The Prevalence of MRI-Defined Sacroiliitis and Classification of Spondyloarthritis in Patients with Acute Anterior Uveitis: A Longitudinal Single-Centre Cohort Study - Bubova, Kristyna; Hasikova, Lenka; Mintalova, Katerina; Gregova, Monika; Kasalicky, Petr; Klimova, Aneta; Brichova, Michaela; Svozilkova, Petra; Heissigerova, Jarmila; Vencovsky, Jiri; Pavelka, Karel; Senolt, Ladislav (Diagnostics (Basel, Switzerland), 2022)
BACKGROUND: Acute anterior uveitis (AAU) is a relatively common extra-musculoskeletal manifestation of axial spondyloarthritis (axSpA); however, data on the prevalence of active sacroiliitis in patients with AAU are limited. METHODS: 102 patients with AAU and 39 healthy subjects (HS) underwent clinical assessment and sacroiliac joint MRI. Patients with absence of active sacroiliitis were reassessed after two years. International Spondyloarthritis Society (ASAS) classification criteria for axSpA (regardless of patient's age) and expert opinion for definitive diagnosis of axSpA were applied. RESULTS: Although chronic back pain was equally present in both groups, bone marrow edema (BME) in SIJ and BME highly suggestive of axSpA was found in 52 (51%) and in 33 (32%) patients with AAU compared with 11 (28%) and none in HS, respectively. Out of all AAU patients, 41 (40%) patients fulfilled the ASAS classification criteria for axSpA, and 29 (28%) patients were considered highly suggestive of axSpA based on clinical features. Two out of the 55 sacroiliitis-negative patients developed active sacroiliitis at the two-year follow-up. CONCLUSIONS: One-third of patients with AAU had active inflammation on SIJ MRI and clinical diagnosis of axSpA. Therefore, patients with AAU, especially those with chronic back pain, should be referred to a rheumatologist, and the examination should be repeated if a new feature of SpA appears.
Keywords: spondyloarthritis; axial spondyloarthritis; sacroiliitis; magnetic resonance imaging; peripheral spondyloarthritis; uveitis